A tool for a design-driven innovation approach to more sustainable business models - Tommaso Corà; Lucilla Fazio (Journal of Business Models (JOBM), 2024)
Purpose The growing imperative for sustainable business practices has led to a recognition that companies must transform their business models to encompass economic, social, and environmental value. At the heart of this transformation is the triple bottom line framework, which evaluates business success in the three dimensions of profit, people, and the planet. Simultaneously, design-driven innovation embraces future-oriented approaches that include people and the ecosystem as stakeholders, while evolving the lenses of innovation, namely desirability (planet), feasibility (network), and viability (prosperity). This evolution offers a new perspective that extends the triple bottom line in business model design by considering the feasibility of achieving impactful, original, and useful innovations. We explore a potential method for designing a business model anchored in the conceptualization of design-driven innovation and a tool to support the creative exploration and coherence assessment of more sustainable (than those currently in use) business models.   Design/Methodology/Approach We built on previous knowledge of design, design-driven innovation, and business model design, and merged with insights from our direct experience as design-driven innovation practitioners, including in applying the tools in different instances with client companies.   Findings We propose the Design-Driven Innovation Business Model Canvas, and provide initial anecdotal evidence from its potential to support the creative exploration and coherence assessment of sustainable business models.   Originality/Value Our tool is designed to merge the design-driven innovation perspective with business design requirements to generate more sustainable business models than those currently in use. We also propose a new conceptualization of the three lenses of innovation, which we then relate to the triple bottom line.
Keywords: 650; Design-Driven Innovation; Business Model Design; Sustainable Business Models; Three Lenses of Innovation; Impact; Planet; Prosperity; Network